The learning experiences of mentees and mentors in a nursing school's mentoring programme - Annemarie Joubert; Johanna de Villiers (AOSIS, 2015)
Background: A School of Nursing supports third-year undergraduate students (mentees) by means of a mentoring programme in which critical-care nursing students (mentors) are involved. However, the programme designers needed to find out what gaps were evident in the programme. Objectives: The objectives of the study were to explore and describe the learning experiences of the mentees and mentors and to obtain recommendations for improving the programme. Method: An action-research method was used to develop and to refine the student-mentoring programme and to identify student needs. However, for the purposes of this article a descriptive design was selected and data were gathered by means of a nominal-group technique. Fourteen mentees and five mentors participated in the research. Results: The findings indicated that attention should be paid to the allocation and orientation of both mentors and mentees. Amongst the positive experiences was the fact that the mentees were reassured by the mentor's presence and that a relationship of trust developed between them. In consequence, the mentees developed critical thinking skills, were able to apply their knowledge and improved their ability to integrate theory and practice. Not only did the mentees gain respect for the mentors' knowledge and competence, but they also lauded the mentoring programme as a memorable and vital experience. Conclusion: The findings indicated that several changes would be needed to improve the structure of the mentoring programme before a new group of mentees could be placed in critical-care units.